Analisis Peran Al-Salb dan Al-Ijab dalam Konteks Pemahaman Al-Uslub Al-Hakim pada Q.S Al-Baqarah Ayat 190 - Annisa Ayunda; Nurfasilah Nurfasilah; Harun Al-Rasyid (STIKes Ibnu Sina Ajibarang, 2025)
This article aims to describe the role of Al-Salb and Al-Ijab in understanding Uslub Al-Hakim in Quran Surah Al-Baqarah verse 190. Uslub Al-Hakim, characterized by shifting the conversation to more important matters, often utilizes the contrast between Al-Salb and Al-Ijab. This study specifically analyzes how the contrasting roles of Al-Salb and Al-Ijab within Uslub Al-Hakim create a broad and profound meaning implied in the verse. Through a case study of the relevant verse from Surah Al-Baqarah, the paper will explain how Uslub Al-Hakim shifts the discourse from one subject to another, and will also explain how the mechanisms of Al-Salb and Al-Ijab work to strengthen arguments and draw the reader’s attention. The data for this research is sourced from the Quran and analyzed qualitatively. The findings of this study are expected to contribute new insights into the study of Quranic style and provide a deeper understanding of the language used in the sacred text.